2018
DOI: 10.21608/adjalexu.2018.57878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Evaluation of Immediate Implant Placement With and Without "Bone Rings" in Esthetic Zone

Abstract: INTRODUCTION:Immediate implant placement is now accepted in clinical dentistry for reconstruction of partially or completely edentulous mandible or maxilla. OBJECTIVES:The aim of the study was to evaluate the role of Maxgraft bone rings on the marginal bone level around dental implants placed in fresh extraction sockets. MATERIALS AND METHODS: A randomized clinical trial was carried out on fourteen cases with freshly extracted sockets with age range 20 to 50 years. There were 2 groups, study group and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…A statistically significant difference was established concerning the implant stability quotient throughout this study period. The results of this study are in accordance with similar results demonstrated by Elnebairy et al [ 23 ] The RVG evaluation demonstrated mean mesial bone resorption of 1.22±0.16mm and mean distal bone resorption of 1.14 ± 0.13 mm at the end of the 6th-month postoperative period. The present data agrees with a study conducted by Crespi et al [ 24 ] who demonstrated that after a 24-month follow-up, mean mesial and distal bone loss was 1.16±0.32mm and1.17±0.41mm, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…A statistically significant difference was established concerning the implant stability quotient throughout this study period. The results of this study are in accordance with similar results demonstrated by Elnebairy et al [ 23 ] The RVG evaluation demonstrated mean mesial bone resorption of 1.22±0.16mm and mean distal bone resorption of 1.14 ± 0.13 mm at the end of the 6th-month postoperative period. The present data agrees with a study conducted by Crespi et al [ 24 ] who demonstrated that after a 24-month follow-up, mean mesial and distal bone loss was 1.16±0.32mm and1.17±0.41mm, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…However, our results are less than Janyaphadungpong et al 38 evaluated implant stability in simultaneous GBR in the posterior mandible and found mean ISQ values of 72.55 ± 3.10 and 76.20 ± 2.68 at two and three months, respectively. Furthermore, the implant stability in our study in group II showed comparable results to Elnebairy et al 39 who conducted a randomized clinical trial to evaluate allograft bone rings around IIP in the aesthetic zone and showed that the mean ISQ value for the allograft ring was 58.0 ± 1.5 immediately after surgery and 68.0 ± 1.4 after 6 months post-surgery. Also, a study published by Pallavi et al 40 used allograft BRT with IIP in the anterior region and showed the mean ISQ score at the time of surgery was 58 ±1.62, and at 6 months, 69 ±1.59.…”
Section: Figure (5): Showing Implant Stability Assessmentsupporting
confidence: 85%
“…Sample Size: Sample size calculation was based on G*power version 3.0.10 to calculate sample size based on the effect size of 1.34, 2-tailed test, α error =0.05, and power 80.0% then total sample size will be 7 cases at least in each group. 26 Methods: The patients were randomly and equally divided into two groups: Group I (control group): involved 7 patients where a titanium mesh-guided bone regeneration was used for ridge augmentation with simultaneous immediate implant placement. Group II (study group): involved 7 patients where an allogeneic bone ring was used for ridge augmentation with simultaneous immediate implant placement.…”
Section: Methodsmentioning
confidence: 99%
“…Symphysis area offers a sufficient amount of cortico-cancellous autogenous bone in addition to its easy access under local anesthesia. For achieving accuracy in selection of implant length, diameter, exact site, angulation without endangering the nearby vital structures and increase success rate with less operative time and less operator skill by using preoperative computerized virtual planning of donor and recipient surgical sites and fabrication of surgical guided stent (15) . Statistical analysis of CBCT images linear measurements in our study revealed that, there was a significant decrease in 3D dimensions of vertical bone height from immediate to 6 months with high percentage of bone resorption.…”
Section: Discussionmentioning
confidence: 99%